2008
DOI: 10.1080/10610270701302465
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular ChemistryIn Silico

Abstract: Computational protocols capable of modelling supramolecular complexes have been evaluated. The complexation of cations by crown ethers and quaternary ammonium ions by an oxacalix[3]arene are presented as examples. In the latter case reliable qualitative results were obtained using the semi-empirical PM3 method where guest LUMO and electrostatic potential energies have been shown to correlate with experimental binding data. The optimal method for more accurate results combines semi-empirical equilibrium geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…While it is possible to use gas phase simulations to describe supramolecular complexes in organic solvents (43,44), due to the extensive hydrogen bonding that could exist in the α-CD complexes an explicitly solvated approach was adopted. The simulation shows that the methyl 6) and are similar in magnitude to both modelled (45) and experimental intramolecular α-CD hydrogen bonds (46,47).…”
Section: Gb Inclusion In α-Cdmentioning
confidence: 99%
“…While it is possible to use gas phase simulations to describe supramolecular complexes in organic solvents (43,44), due to the extensive hydrogen bonding that could exist in the α-CD complexes an explicitly solvated approach was adopted. The simulation shows that the methyl 6) and are similar in magnitude to both modelled (45) and experimental intramolecular α-CD hydrogen bonds (46,47).…”
Section: Gb Inclusion In α-Cdmentioning
confidence: 99%
“…To further investigate any possible complexation between hexahomotrioxacalix[3]arene ureas 1 and 2 and the NACs, they were subjected to computational analysis. The calixarenes, NAC guests and their complexes were built in Spartan 20 [ 26 ] and geometry optimised using molecular mechanics (MMFF) before gas phase semiempirical calculations (PM6) were undertaken using our previously published methods [ 27 , 28 ]. The resulting structures ( Figures S18 and S19 ) indicate the possibility of interactions in some cases, so the thermodynamics of the systems were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The latter calculations encountered problems upon refinement at semi-empirical level so discussion has been restricted to the gas phase results. We have previously shown that, at this level of theory, solution phase host–guest complexes are quite adequately represented by gas phase models [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%